1998
DOI: 10.1136/bjo.82.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive use of mitomycin C on endoscopic lacrimal surgery

Abstract: Adjunctive use of a wound healing inhibitor is considered to increase the success rate of endoscopic endonasal DCR. Its intraoperative use seems to be easy and safe. But the study of this limited series shows no benefit in using it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…The contribution of antifibrotic agents, such as mitomycin C, to the success rate of both external and endonasal DCR surgery has been previously reported [19,20]. In this study, all of the cases showed fibrosis over the surgical area due to previous surgeries; however, none of the cases had been treated with antifibrotic agents.…”
Section: Discussionmentioning
confidence: 47%
“…The contribution of antifibrotic agents, such as mitomycin C, to the success rate of both external and endonasal DCR surgery has been previously reported [19,20]. In this study, all of the cases showed fibrosis over the surgical area due to previous surgeries; however, none of the cases had been treated with antifibrotic agents.…”
Section: Discussionmentioning
confidence: 47%
“…Of these 19 articles, 8 were noncomparative case series [23]–[30] and not suitable for inclusion in the meta-analysis (Table 1). The left 11 comparative studies (including 9 RCTs and 2 non-RCTs) which met our inclusion criteria were included in the final meta-analysis [10]–[15], [31][35].…”
Section: Resultsmentioning
confidence: 99%
“…The dose of MMC used ranged between 0.2 and 0.5 mg/mL, which was placed on the ostium for 2 to 15 minutes. Silicone tubes were used in five studies [11], [14], [15], [31], [35]. Table 2 presents the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zilelioglu и соавт. [9] впервые применили мито-мицин-С в дакриологии после выполнения стандартной эндоскопической эндоназальной ДЦР (ЭДЦР). В область сформированной ДС авторы помещали хирургическую губку, обработанную раствором митомицина-С в концен-трации 0,5 мг/мл, на 2,5 мин таким образом, чтобы вся окружающая слизистая оболочка находилась в контакте с ней.…”
unclassified